Spectral properties of Titan's impact craters imply chemical weathering of its surface. Issue 10 (26th May 2015) - Neish, C. D.; Barnes, J. W.; Sotin, C.; MacKenzie, S.; Soderblom, J. M.; Le Mouélic, S.; Kirk, R. L.; Stiles, B. W.; Malaska, M. J.; Le Gall, A.; Brown, R. H.; Baines, K. H.; et al.
Abstract We examined the spectral properties of a selection of Titan's impact craters that represent a range of degradation states. The most degraded craters have rims and ejecta blankets with spectral characteristics that suggest that they are more enriched in water ice than the rims and ejecta blankets of the freshest craters on Titan. The progression is consistent with the chemical weathering of Titan's surface. We propose an evolutionary sequence such that Titan's craters expose an intimate mixture of water ice and organic materials, and chemical weathering by methane rainfall removes the soluble organic materials, leaving the insoluble organics and water ice behind. These observations support the idea that fluvial processes are active in Titan's equatorial regions.